Faecalibacterium prausnitzii produces butyrate to decrease c-Myc-related metabolism and Th17 differentiation by inhibiting histone deacetylase 3. (27th February 2019) - Zhang, Mingming; Zhou, Lixing; Wang, Yuming; Dorfman, Robert Gregory; Tang, Dehua; Xu, Lei; Pan, Yida; Zhou, Qian; Li, Yang; Yin, Yuyao; Zhao, Shimin; Wu, Jianlin; et al.
Abstract: Decreased levels of Faecalibacterium prausnitzii ( F. prausnitzii ), whose supernatant plays an anti-inflammatory effect, are frequently found in inflammatory bowel disease (IBD) patients. However, the anti-inflammatory products in F. prausnitzii supernatant and the mechanism have not been fully investigated. Here we found that F. prausnitzii and F. prausnitzii -derived butyrate were decreased in the intestines of IBD patients. Supplementation with F. prausnitzii supernatant and butyrate could ameliorate colitis in an animal model. Butyrate, but not other substances produced by F. prausnitzii, exerted an anti-inflammatory effect by inhibiting the differentiation of T helper 17 (Th17) cells. The mechanism underlying the anti-inflammatory effects of the butyrate produced by F. prausnitzii involved the enhancement of the acetylation-promoted degradation of c-Myc through histone deacetylase 3 (HDAC3) inhibition. In conclusion, F. prausnitzii produced butyrate to decrease Th17 differentiation and attenuate colitis through inhibiting HDAC3 and c-Myc-related metabolism in T cells. The use of F. prausnitzii may be an effective new approach to decrease the level of Th17 cells in the treatment of inflammatory diseases. Abstract : Butyrate from gut F. prausnitzii suppresses Th17-mediated IBD